Constitutional Regulation of the Legal Status of Parliamentary Committees and/or Commissions via the Example of Ukraine and Foreign Countries - Кунець, Ірина Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article is concerned with the analysis of the constitutional provisions dealing with the issue of activities of parliamentary committees/commissions. Different extent of regulation of this issue was studied via the example of different countries. It was concluded about the positive experience that can be adopted in making changes to the national legislation. Formulation of the Problem. Individual aspects of activities of parliamentary committees and/or commissions in Ukraine and foreign countries during different historical periods have been repeatedly studied by scientists both in our country and abroad. Nevertheless, the issue of the constitutional regulation of the legal status of the committees and/or commissions and its specifics in different countries has not been highlighted in deep. Examination of the mentioned aspect will contribute to the deeper understanding of the specifics of the legislative regulation of the legal status of parliamentary committees and/or commissions as a structural element of the parliament, for the purpose of further use of the positive international experience to improve the Ukrainian legislation. Presenting the Basic Material. Analysis of the constitutions of Ukraine and foreign countries in terms of the regulation of activities of parliamentary committees and/or commissions allows grouping the countries depending on the regulations fixed in the Fundamental Law, based on specific criteria. In terms of the organizational criterion, the countries can be subdivided into: а) countries, in whose parliaments only committees are created; b) countries, in whose parliaments both committees and commissions are created; c) countries, in whose parliaments only commissions are created. Approaches to the constitutional regulation of the issue of activities of parliamentary committees and/or commissions in Ukraine and foreign countries are rather different. In terms of the constitutional level regulation of the issues of activities of parliamentary committees and/or commissions, the following countries should be distinguished, where: 1) there is no regulation of the issue of activities of parliamentary committees and/or commissions at the constitutional level; 2) there are regulations related to committees and/or commissions fixed in the national Fundamental Law. In terms of the completeness of regulation of the issues of activities of parliamentary committees and/or commissions, the following countries may be distinguished, where: 1) there is no detailed regulation in their constitutions of the issues of activities of such structural elements as parliamentary committees and/or commissions; 2) the issue of activities of such structural elements as parliamentary committees and/or commissions has been regulated in detail in their constitutions. It should be noted that constitutions of different countries have their specifics in the regulation of the said issue, which specifics are described in this article. Conclusions. Analysis of the constitutions of countries across the world allows to conclude that the approach to the regulation of activities of parliamentary committees and/or commissions is rather different. In some countries, the legislator does not regulate this issue at the level of the national Fundamental Law, while in other countries the scope of regulation is so much considerable that covers all the business areas of the committees and/or commissions as structural elements. In our opinion, activities of parliamentary committees and/or commissions should be governed by the national constitution, however excessive detailing will burden the text of the document and make it difficult for perception. There is a positive experience in regulating the number and quantitative composition of the committees and/or commissions, which adds the clarity and accuracy to this parliamentary structure and complicates the possibility of creating the said authorities taking into account the number of those wishing to chair them.